Characterization and scoring of skin changes in severe acute malnutrition in children between 6 months and 5 years of age. (15th October 2015) - Heilskov, S.; Vestergaard, C.; Babirekere, E.; Ritz, C.; Namusoke, H.; Rytter, M.; Deleuran, M.
Abstract: Background: Severe acute malnutrition is a life‐threatening condition. It can be associated with severe skin changes, first properly described by Williams in 1933. The aetiology of these skin changes is still unknown and their character has never been systematically described in dermatological terms. The skin changes have been shown to be a predictor of mortality in hospital care. Systematic investigations on the character of the skin changes that have effect on prognosis, are needed to investigate which of the skin changes that are relevant to improve treatment. Objectives: Our main objective was to identify the skin changes characteristic of children with severe acute malnutrition and to develop a clinical score that describes the morphology and severity in dermatological terms. We also investigated if any of the different skin changes were connected to prognosis. Materials and methods: At Mulago Hospital, Mwanamugimu (Department of Paediatrics and Child Health), Uganda, 120 children were included over a period of six months and observed when treated for severe acute malnutrition. Skin changes were registered through clinical examination and photo documentation and associated to prognosis using Cox and logistic regression analysis. Results: Skin manifestations were characterized by five objective skin signs: telogenic effluvium, pigmentary changes (hyper‐ and hypo‐pigmentation), ichthyosiform skin changes, lichenoid skin changes and bullae‐erosion‐desquamation. The skin changes could be registered in a systematic manner using our simple clinical score. Lichenoid skin changes were a significant predictor of death and allowed improved accuracy of prediction of mortality. Conclusions: The clinical score is simple and practical. A standardized way to register and score the skin changes, will allow a more unified way of reporting results in future studies. The standardization of observations, obtained through the proposed scoring system, will enable comparison of study results in the future.